The Efficacy of Brainspotting Therapy for the Treatment of Tantrum in Young Children - Ningrum, Diah (Jurnal Pendidikan Anak, 2022)
Tantrum appears mainly at the age of 2-4 years old. This behavior is also found in children past 4 years of age. Even though tantrum is the most common behavior problem in young children, they can also cause behavior issues in the future, such as; becoming withdrawn, violent, or having a verbal outbursts and antisocial behavior. In that case, psychological intervention is needed. This study uses a new approach of Brainspotting therapy to treat tantrums in young children. Bainspotting is a psychotherapeutic model that has been conceptualized as a brain and body-aware relational attunement process. Thus, the study's main objective is to determine whether Brainspotting is an effective alternative approach to address the issue of tantrums in young children. A study case of the qualitative method was applied, and data was collected by observing the progress of a 6 years old's child each session, interviewing and comparing assessment of present challenges of a child before and after 10 sessions. The result indicates that Brainspotting is effective as an alternative to reducing tantrums and developing emotional regulation in young children.